Effect of Service Quality and Customer Satisfaction on Customer Loyalty: A case study of Starbucks in Malaysia - Pérez-Morón, James; Madan, Sahana; Cheu, Jin Yin; Kee, Daisy Mui Hung; Cheong, Li Chiy; Chin, Roger; Cheng, Jie; García, Angela Patricia Muñoz (AIBPM Publisher, 2022)
In today's highly competitive business world, practically all organizations recognize that high service quality is a critical weapon for gaining a competitive advantage. A business with high service quality will guarantee a high level of customer satisfaction and build customer loyalty. In this paper, the researchers aim to investigate how service quality and customer satisfaction influenced customer loyalty of Starbucks in Malaysia. Furthermore, this research adopts a questionnaire-based survey. A total of 100 observations were obtained and the gathered data were analyzed using SPSS. Besides, this study has offered new insights and suggested practical actions which aim to improve service quality, increase customer satisfaction and retain and create customer loyalty in the fast-food industry.